The Little Data Book on Information and Communication Technology 2008 - World Bank (Washington, DC, 2012)
The little data book on information and communication technology 2008 charts the progress of this revolution for 209 countries around the world. It provides comparable statistics on the sector for 2000 and 2006 across a range of indicators, enabling readers to readily compare countries. This guide includes indicators covering the economic and social context, the structure of the information and communication technology sector, and sector performance related to access, quality, affordability, institutional efficiency, and applications. The glossary contains definitions of the terms used in the tables.